Angiographic Significance of ST Depression in Anterior Leads in Acute Inferior ST Elevation Myocardial Infarction. - Simkhada, Rabindra; Khan, Barkadin; KC, Sanjay Singh; Budhathoki, Arjun; Adhikari, Krishna Chandra; Baral, Bishow Raj (Nepalese Heart Journal, 2021)
Background and aims: Electrocardiogram of acute ST elevation inferior myocardial infarction can show concomitant ST depression in anterior leads. We aimed to see its significance on coronary angiogram. Methods: Cross sectional study conducted in Department of Cardiology of Shahid Gangalal National Heart Centre from March 2021 to June 2021. Total of 64 patients of acute inferior myocardial infarction were included consecutively. Electrocardiogram were analyzed for the presence of ST depression in anterior leads (V1-V6). Coronary angiogram were obtained. Linear regression analysis was applied to see correlations. Results: Thirty-four (53.12%) participants had significant ST depression in anterior leads. Their mean age was 64.53±11.67 years. Twenty-two (64.70%) were male. Out of them, 13 (38.23%) were hypertensive, 9 (26.47%) were smoker and 7 (20.58%) were diabetic. Among 30 (46.88%) participants without ST depression, mean age was 56.73±13.31 years and 21 (70%) were male. Out of them, 11 (36.66%) were hypertensive, 12 (40%) were smoker and 11 (33.66%) were diabetic. Culprit vessel was right coronary artery in 22 (64.70%) of those with ST depression and 22 (73.33%) of those without ST depression. Significant left anterior descending artery lesion was seen in 19 (55.88%) of those with ST depression and 3 (10%) of those without depression. Anterior ST depression showed positive correlation with left anterior descending artery lesion. Conclusion: ST depression in anterior leads in acute inferior myocardial infarction can be due to presence of concomitant left anterior descending coronary artery disease.